Talent management: an escalating strategic focus in Bangladeshi banking industry - Hosen, Sharif; Islam, Md Asadul; Arshad, Mohd Mursyid; Md Khan, Arif; Alam, Md. Kausar (Human Resource Management Academic Research Society, 2018)
The aim of this study is to justify the talent management (TM) system in a Bangladeshi Commercial Bank. Hence, previous research articles have been reviewed and primary data relating to selected bank have been collected from semi-structured interviews and some reliable and updated secondary sources for selected Bank’s website and other sites of Bangladesh Central Bank to achieve the aim of the study. The study finds several key practices of TM that includes recruitment, talent development, knowledge management, social media, performance management, and rewards. The limitation of this study is that this study is not empirically tasted. The scope of the study focuses on banking sector in Bangladesh. The study recommends that HR managers should embrace TM practices of the case bank to effectively manage their workforce. This study is the first study to uphold TM in banking sector of Bangladesh.